1994
DOI: 10.1084/jem.179.6.1809
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, cDNA cloning, and overexpression of a 33-kD cell surface glycoprotein that binds to the globular "heads" of C1q.

Abstract: SummaryThis work describes the functional characterization, cDNA cloning, and expression of a novel cell surface protein. This protein designated gClq-R, was first isolated from Raji cells and was found to bind to the globular "heads" of Clq molecules, at physiological ionic strength, and also to inhibit complement-mediated lysis of sheep erythrocytes by human serum. The NHzterminal amino acid sequence of the first 24 residues of the Clq-binding protein was determined and this information allowed the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
323
2
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(334 citation statements)
references
References 37 publications
8
323
2
1
Order By: Relevance
“…p32 has both mitochondrial and non‐mitochondrial localization, although p32 predominantly targets to mitochondria with an N‐terminal mitochondria‐targeting sequence 25. In this study, we have fractionated the cell lysate into mitochondria and cytosol and found that p32 was abundantly presented in the mitochondria.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…p32 has both mitochondrial and non‐mitochondrial localization, although p32 predominantly targets to mitochondria with an N‐terminal mitochondria‐targeting sequence 25. In this study, we have fractionated the cell lysate into mitochondria and cytosol and found that p32 was abundantly presented in the mitochondria.…”
Section: Discussionmentioning
confidence: 83%
“…Although p32 can be existed in multicellular compartments, it is predominantly targeted to mitochondria because of the mitochondrial targeting sequence contained in the 73N‐terminal amino acids 25. Functional studies have shown that p32 is required for the induction of mitochondria‐dependent cell death26, 27 and for the metabolic shift between oxidative phosphorylation and aerobic glycolysis 28.…”
mentioning
confidence: 99%
“…In contrast, the amino terminal, globular domain of C1q binds the 33kDa gC1qR/p33 (gC1qR) (Ghebrehiwet, Lim, Peerschke, Willis, and Reid 1994). gC1qR is a ubiquitously expressed cellular protein (Ghebrehiwet and Peerschke 1998;Ghebrehiwet, Lim, Kumar, Feng, and Peerschke 2001).…”
mentioning
confidence: 99%
“…Polyclonal and monoclonal antibodies to human gC1qR were prepared as described by Ghebrehiwet et al, [8,26]. Rabbit polyclonal antibodies to C1q were raised against purified human C1q.…”
Section: Preparation Of Gc1qr and C1q Antibodiesmentioning
confidence: 99%
“…Three C1q-bps, which interact with the collagen tail of C1q, of molecular masses 126, 57 and 68 kDa, have been described on the surface of neutrophils [4][5][6]. Another C1q-bp, called gC1qR, is known to interact with globular head regions of C1q [7,8]. gC1qR is a highly acidic protein and a Abbreviations used : cC1q, collagen-like tails of C1q ; gC1q, globular heads of C1q ; C1q-bp, C1q-binding protein ; FMLP, N-formylmethioninyl-leucylphenylalanine ; PLC, phospholipase C ; PT, pertussis toxin.…”
Section: Introductionmentioning
confidence: 99%